ANALISIS PEMAHAMAN DAN SIKAP SISWA TERHADAP HUBUNGAN SOSIAL SISWA BERBEDA BUDAYA - Eka Fihayati; Adelina Hasyim; M.Mona Adha (FKIP Unila, 2014)
This research aims to describe and analyze the understanding and attitude of the students towards social relations in different cultures of Class XI IPS students in SMA Negeri 1 Sidomulyo lesson year 2013/2014. Formulation in this study is how the understanding and attitude of the students towards social relations in different cultures students. This type of research is descriptive study using quantitative methods. Population are 144 students and samples taken are 29 students. The result showed the indicators of students understanding that 45 % of respondents argue that students understanding included in the category of not understand. Indicators of students attitude against social intercourse different culture students about 52 % of respondents in a category attitude receive. Indicators of social relations in different cultures students as much as 42% of respondents in category less harmonious relationships.Penelitian ini bertujuan untuk menjelaskan dan menganalisis pemahaman dan sikap siswa terhadap hubungan sosial siswa berbeda budaya kelas XI IPS di SMA Negeri 1 Sidomulyo tahun pelajaran 2013/2014. Rumusan dalam penelitian ini bagaimanakah pemahaman dan sikap siswa terhadap hubungan sosial siswa berbeda budaya. Jenis penelitian ini deskriptif menggunakan metode kuantitatif. Populasi sebanyak 144 siswa, sampel yang diambil 29 siswa. Hasil penelitian menunjukkan indikator pemahaman siswa bahwa 45% responden berpendapat bahwa pemahaman siswa masuk dalam kategori kurang memahami. Indikator sikap siswa terhadap hubungan sosial siswa berbeda budaya sebanyak 52% responden dalam kategori sikap menerima. Indikator hubungan sosial siswa berbeda budaya sebanyak 42% responden dalam kategori hubungan kurang harmonis.Kata kunci: berbeda budaya, hubungan sosial, pemahaman, sikap